2000
DOI: 10.1148/radiology.217.2.r00nv44371
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia-Eclampsia: Clinical and Neuroradiographic Correlates and Insights into the Pathogenesis of Hypertensive Encephalopathy

Abstract: Brain edema at MR imaging in patients with preeclampsia-eclampsia was associated with abnormalities in endothelial damage markers and not with hypertension level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
216
3
21

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(247 citation statements)
references
References 33 publications
7
216
3
21
Order By: Relevance
“…9,14 It could be because ours is a tertiary care hospital where patients are referred from other centers and also because facilities for neuroimaging are not universally available. Incidence of PRES in eclamptic women is 54.5% in the present study as compared to 62.5% in Nelli et al study, 19.2% in Mayama study. 14,6 In present study mean age of women diagnosed with PRES was 26±5.1 years and common in multigravidas.…”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…9,14 It could be because ours is a tertiary care hospital where patients are referred from other centers and also because facilities for neuroimaging are not universally available. Incidence of PRES in eclamptic women is 54.5% in the present study as compared to 62.5% in Nelli et al study, 19.2% in Mayama study. 14,6 In present study mean age of women diagnosed with PRES was 26±5.1 years and common in multigravidas.…”
Section: Resultscontrasting
confidence: 56%
“…3%).Whereas several studies reported headache and visual disturbances/visual loss to be the common symptoms. 3,4,8,[19][20][21] We observed epigastric pain in 26.7% patients and visual disturbances were present in very few patients (3.3%). Since MRI is safe to use in pregnancy, its widespread utilization enhances the diagnosis of PRES in eclamptic women with neurological findings (Figure 2a-2d).…”
Section: Figure 1: Persistent Symptomsmentioning
confidence: 65%
See 1 more Smart Citation
“…3,4 Tonic-clonic seizures are not mandatory for the diagnosis of PRES and pre-eclamptic women may demonstrate signs, symptoms and imaging features of PRES in the absence of an eclamptic seizure. [5][6][7] The incidence and possible sequelae of PRES in women with pre-eclampsia are unknown, because cerebral imaging in such women is not standard practice. Whether long-term cerebrovascular outcome, such as stroke, in formerly pre-eclamptic women is a result of the constitutionally increased risk for cardiovascular disease ª 2012 The Authors BJOG An International Journal of Obstetrics and Gynaecology ª 2012 RCOG in these women, 1,2 or whether the pre-eclamptic pregnancy and episode of PRES are additional risk factors, remains speculative so far.…”
Section: Introductionmentioning
confidence: 99%
“…Schwartz et al (2000) estudando pacientes com eclâmpsia e pré-eclâmpsia, encontraram que os sintomas neurológicos estavam associados com alterações morfológicas nas hemácias e níveis elevados da DHL, achados que indicam hemólise microangiopática sugerindo dano endotelial 24 . Este dano endotelial é considerado como ponto central na fisiopatologia da eclâmpsia e pré-eclâmpsia nos múltiplos órgãos e acredita-se que esteja relacionado com toxinas endoteliais circulantes ou anticorpos contra o endotélio 24 . Ressalta-se que no nosso estudo nenhuma das pacientes com alterações eritrocitárias e aumento da DHL apresentou alteração na RM hepática.…”
Section: Discussionunclassified